2019
DOI: 10.1002/cti2.1084
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing tristetraprolin activity reduces the severity of cigarette smoke‐induced experimental chronic obstructive pulmonary disease

Abstract: Objective. Chronic obstructive pulmonary disease (COPD) is a progressive disease that causes significant mortality and morbidity worldwide and is primarily caused by the inhalation of cigarette smoke (CS). Lack of effective treatments for COPD means there is an urgent need to identify new therapeutic strategies for the underlying mechanisms of pathogenesis. Tristetraprolin (TTP) encoded by the Zfp36 gene is an anti-inflammatory protein that induces mRNA decay, especially of transcripts encoding inflammatory cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 83 publications
0
12
0
Order By: Relevance
“…Future studies will strengthen our observations by assessing the levels of these factors in the lung tissues of COPD patients with different levels of severity using immunohistochemistry. Importantly, our laboratory has consistently demonstrated that the inhalational exposure of mice to 8 weeks of CS recapitulates the hallmark features of human COPD 2,4,18,25,26,28–30,84,95 . To our knowledge, this study represents the most comprehensive CS‐induced COPD pulmonary proteome to date.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Future studies will strengthen our observations by assessing the levels of these factors in the lung tissues of COPD patients with different levels of severity using immunohistochemistry. Importantly, our laboratory has consistently demonstrated that the inhalational exposure of mice to 8 weeks of CS recapitulates the hallmark features of human COPD 2,4,18,25,26,28–30,84,95 . To our knowledge, this study represents the most comprehensive CS‐induced COPD pulmonary proteome to date.…”
Section: Discussionmentioning
confidence: 66%
“…Strikingly, after 8 weeks of chronic CS exposure in experimental COPD, the proteomic profiles of lung tissue revealed 269 unique dysregulated proteins, of which 264 were significantly upregulated. All of the chronic pathological features of human COPD develop at this time point including chronic pulmonary inflammation, airway remodelling with mucus hypersecretion, emphysema and impaired lung function 2–4,18,22,23,25–31,56 . This time point is representative of early GOLD stages 1/2 of COPD, 62 allowing changes to be validated in clinically relevant samples.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Consequently, modulating TTP might provide a promising avenue for the development of inflammation regulatory therapies. Specifically, therapeutic approaches to increase the TTP activity can be expected to ameliorate the course of numerous chronic inflammatory diseases with a previously shown connection to TTP, such as rheumatoid arthritis [ 108 , 114 , 115 ], atherosclerosis [ 116 ], diabetes [ 117 ], inflammatory bowel disease [ 118 ], chronic obstructive pulmonary disease [ 119 ], and autoimmune diseases [ 108 , 120 ]. Since chronic inflammatory diseases are a major health care burden, such approaches appear extremely appealing.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are in line with previous reports in other tissues. For instance, massive infiltration of neutrophils has been shown to occur in the skin of TTP KO mice subjected to psoriasis-like inflammation ( 30 ), whereas reduced airway neutrophilic infiltration was shown in mice genetically modified to express constitutively active endogenous unphosphorylated TTP following challenge with cigarette smoke ( 31 ).…”
Section: Discussionmentioning
confidence: 99%